Exploring artificial intelligence adoption challenges: bridging the technology gap for marketing advancements - Susi Susanti Tindaon; Jonas Meylan Freddy Banurea (IAES International Journal of Artificial Intelligence (IJ-AI), 2026)
Artificial intelligence (AI) holds immense potential to enhance marketing strategies for micro, small, and medium enterprises (MSMEs). However, significant barriers, including financial constraints, limited digital literacy, and inadequate government support, hinder its widespread adoption. This study compares AI adoption challenges across two Indonesian MSME ecosystems; tourism-oriented Bali and agrarian Garut using the diffusion of innovation (DOI) lens and complementary model⎯technology organization environment (TOE), technology acceptance model (TAM), unified theory of acceptance and use of technology (UTAUT). The findings reveal that MSMEs in Bali exhibit characteristics of "early adopters" and "early majority," driven by the demands of the tourism sector. In contrast, MSMEs in Garut align more with "late majority" and "laggard" profiles, constrained by infrastructural and resource limitations. By mapping these regional disparities onto the DOI curve, this study provides actionable insights for policymakers. It advocates for the development of ecosystem-aware, tailored strategies to bridge the digital divide and foster inclusive digital transformation, enabling MSMEs across diverse regions to leverage AI for a sustainable competitive advantage.